Analisis Kualitas Pelayanan dan Persepsi Harga Terhadap Kepuasan Pelanggan Studi Pada PDAM Kabupaten Cirebon - Yudianto, Agus; Hidayat, Riskin (potensio, 2009)
This research is a case study on PDAM Cirebon regency.This study aims to examine the impact of service qualityand price perceptions to customer satisfaction. The samplingtechnique in this study using convenience sampling andobtained a sample of 135 respondents. To measure the statementitems used in this study the Likert scale, with a scale of1-5. Item statement of the variable service quality is 22 items,price perception is 14 items, and customer satisfaction is 8items. Results of validity test using factor analysis showedthat all indicators have a loading factor greater than 0.40 andonly loading on one factor. Results of reliability test showedthat each construct has a Cronbach’s alpha values that canbe received that is above 0.60 as the minimum criteria to beacceptable. Results of hypothesis test indicate that hypothesis1 and 2 supported, which means that the service qualityand price perception has positive influence on customer satisfaction,with their respective significance at 1% and 5%.Keyword: Service quality, Price perception, Customer satisfaction